Analisis Perubahan dan Dampak Penerapan PSAK 216 Terhadap Pengakuan Aset Tetap Sebagai Pengganti PSAK 16 di Indonesia - Anisah; Dita Dwy Cahyani; Jihan Nur Armalia; Muhammad Ridwan; Rinny Meidiyustiani (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to analyze the changes and impacts of implementing PSAK 216 as a replacement for PSAK 16 in the accounting treatment of fixed assets in Indonesia. The research employs a descriptive qualitative method through a systematic literature review of 13 academic studies published between 2021 and 2025. The findings indicate that PSAK 216 enhances transparency, relevance, and comparability of financial reporting, particularly in the recognition, measurement, depreciation, and disclosure of fixed assets. However, implementation challenges remain, including the limited readiness of accounting information systems, insufficient human resource competence, inconsistent recognition of impaired assets, and discrepancies between accounting and taxation standards. The 2023 amendments to PSAK 216 also reduced net income because proceeds from pre-use testing must now be recorded as revenue. Overall, this study highlights that the successful adoption of PSAK 216 requires policy readiness, adequate human resources, and strong managerial commitment to improving the quality of financial reporting in Indonesia.